Lewis Base Catalysis Based on Homoconjugate Addition: Rearrangement of Electron-Deficient Cyclopropanes and Their Derivatives - Babu, Kaki Raveendra; He, Xin; Xu, Silong (Synlett, 2020)
Cyclopropane is one of the most reactive functionalities owing to its intrinsic ring strain. Transition-metal catalysis and Lewis acid catalysis have been extensively used in ring openings of cyclopropanes; however, Lewis base-catalyzed activation of cyclopropanes remains largely unexplored. Upon nucleophilic attack with Lewis bases, cyclopropanes undergo ring cleavage in a manner known as homoconjugate addition to form zwitterionic intermediates, which have significant potential for reaction development but have garnered little attention. Here, we present a brief overview of this area, with an emphasis on our recent efforts on Lewis base-catalyzed rearrangement reactions of electron-deficient cyclopropanes using the homoconjugate addition process.1 Introduction2 DABCO-Catalyzed Cloke–Wilson Rearrangement of Cyclopropyl Ketones3 Hydroxylamine-Mediated Tandem Cloke–Wilson/Boulton–Katritzky Reaction of Cyclopropyl Ketones4 Phosphine-Catalyzed Rearrangement of Vinylcyclopropyl Ketones To Form Cycloheptenones5 Phosphine-Catalyzed Rearrangement of Alkylidenecyclopropyl Ketones To Form Polysubstituted Furans and Dienones6 Conclusion and Outlook
Keywords: Lewis base catalysis; cyclopropanes; homoconjugate addition; rearrangement; vinylcyclopropanes; alkylidenecyclopropanes